Phosphoproteomic evaluation of pharmacological inhibition of leucine‐rich repeat kinase 2 reveals significant off‐target effects of LRRK‐2‐IN‐1. (11th November 2013) - Luerman, Gregory C.; Nguyen, Chuong; Samaroo, Harry; Loos, Paula; Xi, Hualin; Hurtado‐Lorenzo, Andres; Needle, Elie; Stephen Noell, G.; Galatsis, Paul; Dunlop, John; Geoghegan, Kieran F.; Hirst, Warren D.
Abstract Genetic mutations in leucine‐rich repeat kinase 2 (LRRK2) have been linked to autosomal dominant Parkinson's disease. The most prevalent mutation, G2019S, results in enhanced LRRK2 kinase activity that potentially contributes to the etiology of Parkinson's disease. Consequently, disease progression is potentially mediated by poorly characterized phosphorylation‐dependent LRRK2 substrate pathways. To address this gap in knowledge, we transduced SH‐SY5Y neuroblastoma cells with LRRK2 G2019S via adenovirus, then determined quantitative changes in the phosphoproteome upon LRRK2 kinase inhibition (LRRK2‐IN‐1 treatment) using stable isotope labeling of amino acids in culture combined with phosphopeptide enrichment and LC‐MS/MS analysis. We identified 776 phosphorylation sites that were increased or decreased at least 50% in response to LRRK2‐IN‐1 treatment, including sites on proteins previously known to associate with LRRK2. Bioinformatic analysis of those phosphoproteins suggested a potential role for LRRK2 kinase activity in regulating pro‐inflammatory responses and neurite morphology, among other pathways. In follow‐up experiments, LRRK2‐IN‐1 inhibited lipopolysaccharide‐induced tumor necrosis factor alpha (TNFα) and C‐X‐C motif chemokine 10 (CXCL10) levels in astrocytes and also enhanced multiple neurite characteristics in primary neuronal cultures. However, LRRK2‐IN‐1 had almost identical effects in primary glial and neuronal cultures from LRRK2 knockout mice. These data suggest LRRK2‐IN‐1 may inhibit pathways of perceived LRRK2 pathophysiological function independently of LRRK2 highlighting the need to use multiple pharmacological tools and genetic approaches in studies determining LRRK2 function. <boxed-text content-type="graphic" id="jnc12483-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> Genetic mutations in leucine‐rich repeat kinase 2 (LRRK2) have been linked to Parkinson's disease, potentially contributing to the pathogenesis through increased kinase activity acting via phosphorylation‐dependent LRRK2 substrate pathways. To determine the potential pathways, we performed SILAC combined with phosphopeptide enrichment and LC‐MS/MS analysis +/‐ LRRK2 inhibitor. Bioinformatic analysis of those phosphoproteins suggested a potential role for LRRK2 kinase activity in regulating pro‐inflammatory responses and neurite morphology, among other pathways.